Anatomic Referencing Restores the Anatomy of the Distal Femur with Less Compromise - Knapp, Paul W.; Scuderi, Giles R. (The Journal of Knee Surgery, 2023)
Historically, anterior referencing and posterior referencing are two specific techniques that surgeons can use for proper sizing of the femoral component in total knee arthroplasty (TKA). In this review, we introduce the concept of “anatomic referencing” which has become useful with more incremental sizes of the femoral component to more perfectly match the native anatomy of each patient and reduce overstuffing of the patellofemoral joint and medial-lateral (ML) overhang. Fifty consecutive TKA cases were reviewed where the novel anatomic referencing technique was used. Lateral radiographic projections were obtained preoperatively and postoperatively. The posterior condylar offset (PCO) was evaluated on the lateral radiographs by measuring the distance between the tangent line of the femoral diaphysis posterior cortex and the posterior condylar margin. PCO ratio (PCOR) was calculated by dividing the PCO by the distance between the posterior condylar border and a tangent line along the anterior cortex of the femoral diaphysis. Forty-five patients (50 TKAs) were reviewed. Average age of the patients was 70.34, range: 47–91. There were 19 males and 26 females reviewed in this series. On average, the delta PCOR was 0.022 (standard deviation = 0.032; min: –0.049, max: 0.082). When grouping our results into three main groups: < –0.03, –0.03 to 0.03, and > 0.03, we found that 62% fell within the –0.03 to 0.03 range. There was no statistically significant difference in delta PCOR between standard and narrow implants (p = 0.418). The proposed novel anatomic referencing technique has allowed for proper sizing of patients' femurs in the anteroposterior and ML direction while avoiding component overhang or the need for component downsizing to obtain a proper ML fit. This radiographic review confirmed this to be a highly accurate and reproducible technique.
Keywords: orthopaedics; knee arthroplasty; knee replacement